Perancangan Alat Sistem Sensor Pendeteksi Hujan Untuk Lingkungan Rumah Menggunakan Arduino Uno - Ariz Prasetyo; Dimas Febriawan (LPPM STIKOM Tunas Bangsa, 2023)
Indonesia, with itThere are two distinct seasons in tropical climates : the rainy season and the dry season and predicting these seasons is not easy.the aim of this is to develop a rain detection tool based on a rain sensor .this project is to develop a rain detection tool based on a rain sensor, buzzer and temperature sensor as the main components. using this simple rain detector prototype method is designed to help detect rain, which is important in Indonesia's unpredictable climate. The process of developing this rain detection device involves three main stages: planning, production, and evaluation. The electronic components used in this tool include a raindrop sensor, buzzer, temperature sensor and LCD screen. The results of the tests carried out show that the device is functioning properly. When it detects rain, the raindrop sensor triggers a buzzer sound, and the LCD indicator lights up while displaying information on the LCD screen. Apart from that, this indicates that the wetter the raindrop sensor, the longer the buzzer sound will be. An Arduino Uno microcontroller is integrated into the device for easy operation. This rain detector serves as an effective solution for detecting rain in Indonesia's unpredictable weather conditions, providing a practical tool for users to stay informed and take necessary precautions during the rainy season.